2018
DOI: 10.1007/s00228-018-2482-9
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review and meta-analysis of risk factors for statin-induced myopathy

Abstract: This comprehensive assessment of risk factors can help support clinicians in reducing the incidence of SIM in their patient population on statins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 44 publications
3
36
1
4
Order By: Relevance
“…Nonetheless, not every patient who is affected carries such polymorphisms. Studies have also demonstrated an effect of statin-induced myopathy on the disturbances in homeostasis of calcium, reduced cholesterol synthesis at the cellular level, and an increase in expression of HMG-CoA reductase inhibitors [6]. Another attribution of statin-induced myopathy is the part played by mitochondria, where a dysfunctional or decreased coenzyme-Q10 synthesis might play a role [7].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, not every patient who is affected carries such polymorphisms. Studies have also demonstrated an effect of statin-induced myopathy on the disturbances in homeostasis of calcium, reduced cholesterol synthesis at the cellular level, and an increase in expression of HMG-CoA reductase inhibitors [6]. Another attribution of statin-induced myopathy is the part played by mitochondria, where a dysfunctional or decreased coenzyme-Q10 synthesis might play a role [7].…”
Section: Discussionmentioning
confidence: 99%
“…The case reports presented in this review identified very well-known risk factors for rhabdomyolysis suspected to be due to macrolides-statins combination. Advanced age, cardiovascular diseases, renal impairment, DM, and concomitant interacting drugs are all considered risk factors for the development of statin-induced rhabdomyolysis with or without concomitant macrolides 57,70,71,83…”
Section: Discussionmentioning
confidence: 99%
“…In another review of case reports of statin-induced rhabdomyolysis, most cases of simvastatin-induced rhabdomyolysis occurred at a dose of 40 mg 71. Also, Nguyen et al found that the OR of developing simvastatin-induced rhabdomyolysis was significantly increased when the simvastatin dose was larger than 20 mg 70. Clarithromycin was the most suspected offending agent in more than 50% of the cases, followed by erythromycin, while azithromycin was implicated in only one case.…”
Section: Case Reports From the Literaturementioning
confidence: 99%
See 2 more Smart Citations